Sucralose Stimulates Mitochondrial Bioenergetics in Caco-2 Cells - Bórquez, Juan Carlos; Hidalgo, Miltha; Rodríguez, Juan M.; Montaña, Alejandra; Porras, Omar; Troncoso, Rodrigo; Bravo-Sagua, Roberto (Frontiers in Nutrition, 2021)
Sucralose is a non-caloric artificial sweetener widely used in processed foods that reportedly affects energy homeostasis through partially understood mechanisms. Mitochondria are organelles fundamental for cellular bioenergetics that are closely related to the development of metabolic diseases. Here, we addressed whether sucralose alters mitochondrial bioenergetics in the enterocyte cell line Caco-2. Sucralose exposure (0.5 to 50 mM for 3 to 24 h) increased cellular reductive power assessed through MTT assay, suggesting enhanced bioenergetics. Low doses of sucralose (0.5 and 5 mM) for 3 h stimulated mitochondrial respiration, measured through oxygraphy, and elevated mitochondrial transmembrane potential and cytoplasmic Ca2+, evaluated by fluorescence microscopy. Contrary to other cell types, the increase in mitochondrial respiration was insensitive to inhibition of mitochondrial Ca2+ uptake. These findings suggest that sucralose alters enterocyte energy homeostasis, contributing to its effects on organismal metabolism.